Design and Implementation of an Arduino Based Light Dependent Alarm System - Ibrahim, H.; Mohammed, A. A.; Aliyu, I. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This paper is based on design and implementation of an Arduino based alarm system which is capable of monitoring the illumination of the surrounding automatically. Once the presence or absence of light is detected accordingly, a control device is activated which sends a sound alarm to a buzzer connected to the output of the system. Waking up early from sleep has always become a challenge most especially after a very hectic and busy engagement during the previous day time, this makes waking up early the next morning to meet up with the activities of the day a challenge. The components used for carrying out this study include Light Dependent Resistor, a control unit and an output buzzer unit. The LDR works on the principle of change of resistance based on the amount of luminous energy in its environment at that moment of time, once an illumination is detected, an Arduino Uno board was used to send a signal to the buzzer that generates sound when the intensity of light increases. The test conducted showed that the LDR resistance decreased as illuminance on the LDR increased; the illuminance ranges at which the buzzer was triggered was between 100-1000lux.